Pengaruh Elektronik Word of Mouth (E-WOM) and Brand Image Terhadap Keputusan Pembelian Konsumen Milenial di Bandung Pada era Pandemic Covid - 19 - Asaretkha Adjane Annisawati; Senny Handayani Suarsa (Jurnal Sekretaris dan Administrasi Bisnis, 2023)
This study aims to determine the effect of electronic word of mouth and brand image to purchase decisions of millennial customer in Bandung during the Covid-19 pandemic with a case study: e-commerce Shopee. This type of research is descriptive and associative. The population in this study are millennial customers in Bandung who actively use Shopee e-commerce. The research sample was 100 respondents and data analysis using SMART PLS. The results of this study indicate that the E-wom (X1) and the Brand Image (X2) have a positive and significant effect on Shopee’s millennial customer purchase decisions in Bandung during the Covid-19 pandemic era as much as 96%.